Efficient Mobility Management Framework for Wireless Sensor and Actor Networks - Venkatalakshmi, M.; Ponnusamy, R. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
In contemporary communication systems, mobile sensor along with actor networks (WSANs) are essential because they allow dynamic incorporation between sensor that is being tested and actor nodes for uses like automation in factories acholarnd environmental surveillance. This study uses MATLAB's computational power to provide a thorough methodology for handling mobility optimization in WSANs. The main issues with energy efficiency, maintaining connectivity, and changing event response are covered by the suggested framework. The optimization issue is mathematically formulated with the goals of maximizing connectivity, minimizing consumption of energy, and successfully responding to dynamic events. Mobility models that are energy-aware are created by taking into account variables like node velocity, distance drove, and rate of energy consumption. Real-time mechanisms react to dynamic events, and adaptive protocols for interaction are used to maintain connectivity. The optimal solution problem is solved using MATLAB's optimizing toolbox, which includes constraints derived from mobility rules and WSAN changes. The framework's effectiveness in various scenarios is confirmed by comprehensive simulations, and an examination of comparisons shows that it outperforms current methods.